Planning for regional sustainability and justice: The role of collective impact. Issue 3 (27th May 2019) - Reece, Jason; Gough, Meghan Z.
ABSTRACT: In order to incentivize regional sustainability planning efforts, in 2010 and 2011 the US Department of Housing and Urban Development awarded Sustainable Communities Initiative Regional Planning Grant (SCI-RPG) program grants. SCI presented a unique model of supporting community development goals at a regional scale, with an emphasis on marginalized communities. This study considers the SCI-RPG program through a lens of collective impact, examining our understanding of collective impact and the implications for regional planning for sustainability and justice. We find that the SCI experience incorporates components of collective impact and presents a unique iteration of collaborative governance, which we refer to as "collective impact regionalism." We find that this process leads to beneficial outcomes to support planning for long-term sustainability, justice, and diverse community development goals but is resource intensive and can be undermined by poor implementation planning.